Toward perpetual peace - Béjar, Nélida (Trinity College (Dublin, Ireland). Department of Music, 2012)
This is a thesis for the degree of Doctor of Philosophy in music composition. In the opening part (A), 1 comment on my musical background, environment and influences, including a shorter comment on the orchestra piece Kilter as an example for an earlier, non-staged, instrumental piece. The main part (B) consists of the comment and analysis of the music theatre Toward Perpetual Peace (original German title: Zum Ewigen Frieden - Ein Abgesang), a “staged requiem” written and performed in 2010.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin